SIMULASI PENGGUNAAN LAHAN DALAM PEMODELAN KESETIMBANGAN TATA AIR DI DAERAH ALIRAN SUNGAI BLORONG KABUPATEN KENDAL - Sriyono Sriyono; Dewi Liesnoor Setyowati (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2006)
Flooded area ofBlorong River increased. Delusion area of the flooded area was 0.5 meter and became 1.5 meters high. Result ofthe research namely TATA-AIR.EXE, base concept of modeling uses water balance was made by using Delphi 7'' version. Correlation test value between modeled discharge flow and field measurement result showsr-counting value (0.99) higher than r-table(0.576), hence the model is can be used for simulating various landuse alternative. The simulation result using TATA· AIR.EXE shows that entire alternatives for model experimentation resulted discharge ratio value was under 30. condition ofBlorong River discharge was in the range between 5.29 until 5.94, therefore it is assumed normally, even it can be assumed very good value. Floods in the downstream of Blorong River is caused by drainage capacity and the flooded area in the downstream is topographically located on the low-flat area (close to the sea) which cannot store the running water flow from the upstream ofBlorong catchment area.